Molecular characterisation of sago starch using gel permeation chromatography multi-angle laser light scattering - Zainon Othman,; Saphwan Al-Assaf,; Osman Hassan, (Universiti Kebangsaan Malaysia, 2010)
The molecular characteristics of sago starch (native and debranched) were determined using a gel permeation chromatograpy multi-angle laser light scattering (GPC-MALLS) method. The method involves the optimisation of sample solubilisation and GPC operating conditions. The weight-average molecular weight Mw of native and debranched sago starch determined was 29.1 ± 2.1 °— 106 and 1.87 ± 0.4 °— 105 gmol-1 respectively while radius of gyration Rg was 123.6 and 59.3 nm respectively. The reduction in Mw and Rg in debranched sago was attributed to the hydrolysis of α-1,6 glycosidic linkages by pullulanase to smaller oligosaccharides.